PROMOTING CLIMATE CHANGE AWARENESS AMONG COASTAL COMMUNITIES THROUGH ECOLITERACY - Okorie, Christiana Uzoaru (International Journal of Research -GRANTHAALAYAH, 2023)
Climate change has continued to impact on the lives and livelihood of coastal communities in Rivers State. Most of the dwellers are unaware of the roles they are playing towards contribution to the climate change impact. They are oblivious of their actions on the environment as part of the anthropogenic cause of climate change. In other to create the awareness of their contribution towards climate change, it requires development of a new systemic thinking called ecoliteracy, that defines human interrelationship, interdependent and connectedness to the environment. This will amount to a necessary step toward mitigating the effects of climate change and promoting healthy and sustainable coastal community environments. Ecoliterate residents of coastal communities, however, are more likely to take action to protect the environment.